A Pedagogical Approach to Action Research. (March 2014) - Gullion, Jessica Smartt; Ellis, Erin Graybill
Perhaps the best training for students to apply sociology is through hands-on community work. In this article, we write about the experience of a graduate-level qualitative research methods course in taking on an action research project over the course of a semester. We provide a detailed overview of the project along with practical tips for instructors who would like to replicate this pedagogy.